Gaussian Pell-Lucas Polynomials - Yağmur, Tülay (Communications in Mathematics and Applications, 2019)
In this paper, we first define the Gaussian Pell-Lucas polynomial sequence. We then obtain Binet formula, generating function and determinantal representation of this sequence. Also, some properties of the Gaussian Pell-Lucas polynomials are investigated.